Predictors of unsuppressed viral load among adults on follow up of antiretroviral therapy at selected public and private health facilities of Adama town: unmached case-control study - Fraol Jaleta; Bayissa Bekele; Soriya Kedir; Jemal Hassan; Asnakech Getahun; Tadesse Ligidi; Getinet Garoma; Kiflu Itefa; Tadesse Gerenfes; Abera Botore; Berhanu Kenate; Gutu Dagafa; et al. (BMC, 2022)
Abstract Background Despite the scale up of antiretroviral therapy (ART), unsuppressed viral load among population taking ART in private and public health facilities is still a public health concern increasing the risk of treatment failure. Studies comprehensively assessing significant predictors of non-suppressed viral load among patients on follow up of AR in public and private health facilities are limited. The objective of the study was to identify predictors of unsuppressed viral load among adult patients taking antiretroviral therapy at selected public and private health facilities of Adama town, East shewa zone, Ethiopia. Methods An unmatched case-control study was conducted from April 15 /2021 to May 20/2021. A total sample size of 347 patients consisting 116 cases and 231 controls was selected from electronic database among patients who started ART from September 2015 to August 2020. Data were collected using checklist from patient medical records and analyzed by SPSS. The association of dependent and independent variables was determined using multivariate analysis with 95% confidence interval and P - value in logistic regression model to identify independent predictors. Result From the total 347 participants, 140 (40.3%) of them were males and 207 (59.7%) were females. In multivariate logistic regression, CD4 count < 100 [(AOR:1.22, 95% CI: 1.4-7.3)], CD4 100-200[(AOR: 2.58 95% CI: 1.06-8.28)], Fair Adherence [(AOR: 2.44, 95% CI: 1.67-4.82)], poor adherence [(AOR: 1.11, 95% CI: 1.7-6.73)], History of Cotrimoxazole Therapy (CPT) use and not used [(AOR: 2.60, 95% CI: 1.23-5.48)] and History of drug substitution [(AOR:. 361, 95% CI: .145-.897)] were independent predictors of unsuppressed viral load with the p-value less than 0.05. Conclusion and commendation In this study, Baseline CD4, adherence, History of CPT used and history of drug substitution was predictors of unsuppressed viral load. Monitoring immunological response through scheduled CD4 tests is essential to maintain immunity of the patients preventing diseases progression. Intensive adherence support and counseling should conclusively be provided through effective implementation of ART programs by providers would enhance viral suppression ensuring the quality of care and treatment.